2018
DOI: 10.1016/j.ijheh.2018.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Human biomonitoring of polychlorinated biphenyls (PCBs) in plasma of former underground miners in Germany – A case-control study

Abstract: Polychlorinated biphenyls (PCBs) are very persistent organic pollutants of severe environmental concern due to their toxic properties. Former underground miners might have been exposed to this substance group due to the widespread use of PCBs in hydraulic oils from the late 1960s to the mid 1980s. We have conducted a blinded case-control study in order to evaluate the possibility of retrospective exposure assessment of PCBs using human biomonitoring in former underground miners decades after the last possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…The detectable influence of age on internal PCB 74 burden of underground miners is attributed to the relatively long half-life of PCB 74. The same age dependency was noted in by Schettgen et al (2018). However, in this case-control study, a regression analysis indicated that the influence of age on biomonitoring results for PCB 74 and PCB 114 was much lower than the effect of being a former underground miner (cases) or not (controls).…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…The detectable influence of age on internal PCB 74 burden of underground miners is attributed to the relatively long half-life of PCB 74. The same age dependency was noted in by Schettgen et al (2018). However, in this case-control study, a regression analysis indicated that the influence of age on biomonitoring results for PCB 74 and PCB 114 was much lower than the effect of being a former underground miner (cases) or not (controls).…”
Section: Discussionsupporting
confidence: 74%
“…Pearson's Chi-square for at least one congener above reference was 0.13 (p=0.937) and for PCB 74 it was 0.011 (p= 0.994). The differences between individual coal mines in % of participants with a minimum of one congener above the individual reference value and with mining specific (Schettgen et al 2018) PCB 74 above the individual reference also did not show significant differences between mines (see Supplement Figure 1). Due to the small numbers of participants from individual coal mines the Fisher's exact test was applied and showed a value of 46.8 (p=0.41) and 51.6 (p=0.19), respectively, for PCB 74.…”
Section: Regional Distributionmentioning
confidence: 87%
See 3 more Smart Citations